Effect of the pectin contents and nanostructure on the stem straightness of two Paeonia lactiflora cultivars - Yiran Huang; Anqi Ren; Yingling Wan; Yan Liu (PeerJ, 2023)
Herbaceous peony (Paeonia lactiflora Pall.) is an ancient ornamental crop and, in recent decades, an emerging popular cut flower. Straight stems are a vital criterion for cut herbaceous peony selection, while many cultivars bend as the plant develops. Pectin helps maintain the mechanical strength of the cell wall. However, little is known about its role in the stem bending of herbaceous peony. Two herbaceous peony cultivars with contrasting stem morphologies (‘Dong Fang Shao Nv’, upright; ‘Lan Tian Piao Xiang’, bending gradually) at five developmental stages were used as materials to investigate the effects of pectin content and nanostructure on straightness using the carbazole colorimetric method and atomic force microscopy observations. The contents of water-soluble pectin (WSP), CDTA-soluble pectin (CSP), and sodium carbonate-soluble pectin (SSP) differed significantly between the two cultivars, and the contents and angle of the flower and branch showed correlations. For the pectin nanostructure, WSP showed agglomerates and long chains, with a higher proportion of broad agglomerates at the later stages of the bending cultivar than the upright cultivar. CSP showed branched chains, and the proportion of broad chains was higher in the upright cultivar at later stages, while CSP shape changed from agglomerates to chains in the bending cultivar. SSP mainly consisted of short linear main chains, and side chains in the upright stem were stacked, and the bent cultivar had more broad and short chains. It can be concluded that the contents, nanometric shape, and size of the three kinds of pectin are highly likely to affect herbaceous peony stem straightness. This study provides a theoretical basis for the role of pectin in the production and breeding of herbaceous peony cut flowers.